Comparison of intranasal fluticasone spray, budesonide atomizer, and budesonide respules in patients with chronic rhinosinusitis with polyposis after endoscopic sinus surgery. Issue 3 (17th December 2015) - Neubauer, Paul D.; Schwam, Zachary G.; Manes, R. Peter
Abstract : Background: Nasal steroids are a critical part of the management of patients with chronic rhinosinusitis with nasal polyposis (CRSwNP) after endoscopic sinus surgery (ESS). Increasingly, practitioners are using budesonide respules delivered to the sinonasal cavities, which is an off‐label use, in lieu of traditional nasal steroids. There has been little research comparing budesonide with traditional nasal steroids and the most effective delivery method of budesonide. Methods: A randomized controlled trial was performed on patients after ESS for CRSwNP in a tertiary care center. Patients were randomized into 1 of 3 groups: group A received fluticasone nasal spray twice daily; group B received budesonide respules via a mucosal atomization device (MAD) twice daily; and group C received budesonide respules instilled via the vertex‐to‐floor (VF) position twice daily. Primary endpoints were 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and Lund‐Kennedy scores at 6 months. Results: Thirty‐two patients were enrolled in the study, 23 of whom completed the 6‐month trial. There were no significant differences among groups A, B, and C with respect to age, gender, asthma, aspirin sensitivity, or previous ESS. Group B had a statistically significant greater reduction in SNOT‐22 and Lund‐Kennedy scores at the primary endpoint of 6 months compared to groups A and C. Group C had the next greatest reduction, which was statistically significant, followed by group A. Conclusion: Patients treated with budesonide after ESS for CRSwNP had greater improvement in SNOT‐22 and Lund‐Kennedy scores compared to fluticasone at 6 months. The data supports the use of budesonide respules, particularly with a MAD, over fluticasone for CRSwNP patients after ESS.